PENGARUH EDUKASI GIZI TERHADAP PENGETAHUAN GIZI DAN ASUPAN ENERGI, PROTEIN DAN BESI PADA REMAJA - Asmarudin Pakhri; Sukmawati Sukmawati; Nurhasanah Nurhasanah (Politeknik Kesehatan Makassar, 2018)
Bad knowledge leads to nutritional problems. One of the efforts to improve the nutritional status of adolescents is by providing nutritional knowledge about balanced diet so they can achieve optimal health. This study aims to determine the effect of nutritional education on nutritional knowledge, energy, protein and iron intake of adolescents in SMP Negeri 35 Makassar. This research is Quasi Experimental with one pre-test and post-test group design. Samples are 34 students of class VIII selected by cluster random sampling. This study analyzed by paired sample t test. Nutrition education is given by lecture method and discussion using leaflet with frequency 3 times meeting in 3 weeks. The results showed that there is an effect of nutritional education on nutritional knowledge, energy and protein intake with p value = 0,000, p = 0,005 and p = 0,002 (α <0,05), while there is no effect of nutritional education on iron intake With p value = 0,555 (α> 0,05). Nutritional education is useful in improving nutritional knowledge, energy and protein intake. Keywords : Nutritional education, energy, protein, iron intake.